2008
DOI: 10.1111/j.1440-1746.2008.05482.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of human leukocyte antigen polymorphism with outcomes of hepatitis B virus infection

Abstract: HLA-A*33 was closely related with susceptibility to persisting hepatitis B infection, and HLA-DRB1*13 was closely related with protection against persisting hepatitis B in an Iranian population. These findings emphasized that the host HLA polymorphism is an important factor in determining the outcome of HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 14 publications
4
28
0
Order By: Relevance
“…T-cell response (Diepolder et al 1998;Futagawa et al 2006). In a study by Ramezani et al (2008) in Iran, the presence of HLA-DR13 was protective against chronic hepatitis, and HLA class I A33 was associated with the onset of chronic disease, a finding in agreement with many similar studies, including the present one. In the Iranian study the development of chronic disease was associated with age, HBeAg, and anti-HBe.…”
Section: Discussionsupporting
confidence: 93%
“…T-cell response (Diepolder et al 1998;Futagawa et al 2006). In a study by Ramezani et al (2008) in Iran, the presence of HLA-DR13 was protective against chronic hepatitis, and HLA class I A33 was associated with the onset of chronic disease, a finding in agreement with many similar studies, including the present one. In the Iranian study the development of chronic disease was associated with age, HBeAg, and anti-HBe.…”
Section: Discussionsupporting
confidence: 93%
“…We have demonstrated the association of specific HLA alleles susceptible to HBV-related HCC, whereas most previous studies have focused on susceptibility and resistance to chronic hepatitis B (Han et al, 2005). Ramezani et al (2008) showed that HLA-A*33 is strongly related to susceptibility to hepatitis B persistence and that HLA-DRB*13 is strongly related to protection against hepatitis B persistence in a cross-section of the Iranian population. S.R.S.…”
Section: Discussionmentioning
confidence: 78%
“…8 Specifically, the implicated alleles have been previously linked with autoimmune conditions, many of which are also established or hypothesized risk factors for NHL, including systemic lupus erythematosus (HLA-DRB1*0301, HLA-B*0801), Sjogren syndrome (HLA-DRB1*0301, HLA-B*0801), celiac disease (HLA-DRB1*0301), rheumatoid arthritis (HLA-DRB1*0101 and *0401), and type 1 diabetes (HLA-DRB1*0401 and *0301). 9 Previous risk reductions have also been reported for several other diseases in association with HLA-DRB1*13 alleles, including autoimmune conditions (eg, rheumatoid arthritis 10 and multiple sclerosis 11 ) and infectious diseases (eg, hepatitis B infection, [12][13][14] hepatitis C infection, 15,16 and human papillomavirus 17 ). Ours is the first such report for NHL.…”
Section: Zygosity (Heterozygote Advantage)mentioning
confidence: 96%